2020
DOI: 10.1155/2020/7825024
|View full text |Cite
|
Sign up to set email alerts
|

Fast Rate Production of Biodiesel from Neem Seed Oil Using a Catalyst Made from Banana Peel Ash Loaded with Metal Oxide (Li‐CaO/Fe2 (SO4)3)

Abstract: Biodiesel is a possible remedy to the present toxic, finite sources and ever-diminishing crude fuels. Nonedible and locally available (Azadirachta indica) neem seed oil (NSO) as a second-generation feedstock was transformed into biodiesel using calcined banana ash (CBA) derived from banana peels blended with lithium calcium oxide iron (III) sulphate Li-CaO/Fe2 (SO4)3 catalyzed transesterification. Transesterification process was employed to minimize the free fatty acid (FFA) content of NSO to afford 99.8% yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The further decrease of 45.9% was observed at below 700 °C mainly due to the oxidation of the carbonaceous material present in the catalyst releasing carbon monoxide and carbon dioxide . The last degradation, 700–1001 °C, corresponds to a 7.3% weight loss apparently due to decomposition of the metal oxides . Therefore, the calcination temperature of the WPFP was set to 400 °C as presumably pectic polysaccharide as the main component of WPFP (60–70%) has decomposed and the carbonaceous compounds such as K 2 CO 3 which have a similar catalytic activity with the homogeneous basic catalyst reside in WPFP .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The further decrease of 45.9% was observed at below 700 °C mainly due to the oxidation of the carbonaceous material present in the catalyst releasing carbon monoxide and carbon dioxide . The last degradation, 700–1001 °C, corresponds to a 7.3% weight loss apparently due to decomposition of the metal oxides . Therefore, the calcination temperature of the WPFP was set to 400 °C as presumably pectic polysaccharide as the main component of WPFP (60–70%) has decomposed and the carbonaceous compounds such as K 2 CO 3 which have a similar catalytic activity with the homogeneous basic catalyst reside in WPFP .…”
Section: Resultsmentioning
confidence: 99%
“…The last degradation, 700–1001 °C, corresponds to a 7.3% weight loss apparently due to decomposition of the metal oxides . Therefore, the calcination temperature of the WPFP was set to 400 °C as presumably pectic polysaccharide as the main component of WPFP (60–70%) has decomposed and the carbonaceous compounds such as K 2 CO 3 which have a similar catalytic activity with the homogeneous basic catalyst reside in WPFP . Furthermore, Vadery et al (2014) concluded that calcination temperature above 400 °C did not affect the biodiesel conversion using calcined coconut husk ash as the catalyst .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The species has been reported to have significant medicinal uses, as anti-dermatophytes, malaria, asthma, and intestinal worms (Nde et al, 2015), as well as other useful industrial utilizations (Syndia et al, 2015). Some efforts have been made to incorporate the seed oil extracts of this plant in biodiesels (Banu et al, 2018;Madai et al, 2020). The present study, therefore assesses the physico-chemical and fatty acid compositions of crude seed oil extracts of Azadirachta indica as potential biodiesel and industrial substrate.…”
Section: Introductionmentioning
confidence: 99%